2020
DOI: 10.3389/fpsyg.2020.01758
|View full text |Cite
|
Sign up to set email alerts
|

Are Chinese Teams Like Western Teams? Indigenous Management Theory to Leapfrog Essentialist Team Myths

Abstract: Our study analyzes a gap in research on Chinese and Western management teams, based on a broad literature review. We claim that prevalent theoretical perspectives in the management team literature might be biased toward a Western-centric view of team dynamics. This obscures alternative ways of understanding top teams encompassing Chinese cultural traditions. We outline how an essentialist team conceptualization leads to a paradox consisting of three mutually contradicting myths. Myth 1 implies that Western gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 130 publications
(221 reference statements)
1
14
0
Order By: Relevance
“…The purpose of this study was to explore the influence of two widely different languages (English and Chinese) on mono- and bilingual subjects’ ability to predict and explain a commonly occurring communication barrier in management involving Chinese and Western participants as earlier described in research ( Smith et al, 1997 ; Chen and Tjosvold, 2005 , 2006 , 2007 ; Wilkinson et al, 2005 ; Arnulf, 2014 ; Arnulf and Kristoffersen, 2014 ; Casas Klett and Arnulf, 2020 ). In particular, the focus of the study was on how cognitive and meta-cognitive characteristics of the languages may obstruct the dialogue process while at the same time making it difficult for the organizational participants to overcome the communication barrier.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The purpose of this study was to explore the influence of two widely different languages (English and Chinese) on mono- and bilingual subjects’ ability to predict and explain a commonly occurring communication barrier in management involving Chinese and Western participants as earlier described in research ( Smith et al, 1997 ; Chen and Tjosvold, 2005 , 2006 , 2007 ; Wilkinson et al, 2005 ; Arnulf, 2014 ; Arnulf and Kristoffersen, 2014 ; Casas Klett and Arnulf, 2020 ). In particular, the focus of the study was on how cognitive and meta-cognitive characteristics of the languages may obstruct the dialogue process while at the same time making it difficult for the organizational participants to overcome the communication barrier.…”
Section: Discussionmentioning
confidence: 99%
“…This study was designed to avoid the possibility of culture blindness that has been shown to be prevalent in studies using Likert-scale measurement instruments ( Kamnerdmongkhol and Bjørnstadjordet, 2019 ; Arnulf and Larsen, 2020 ; Casas Klett and Arnulf, 2020 ). To ensure sensitivity to the cultural differences in focus, the design is experimental in nature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations